Effects of post-bleeding vascular infusion of cattle with a solution of sugars, sodium chloride, and phosphates with or without vitamin C on carcass traits, Warner-Bratzler shear forces, and palatability - E.J. Yancey; T.E. Dobbels; E. Katasanidis; Michael E. Dikeman; Edgar Chambers IV (Kansas Agricultural Experiment Station Research Reports, 1999)
Two groups of grain-finished, crossbred Charolais steers were utilized to determine the effects of post-bleeding vascular infusion on dressing percentages, USDA quality and yield grades, Warner-Bratzler shear force values, and flavor. Nine steers from one group of 18 were infused with a solution containing sugars, sodium chloride, and a phosphate blend (MPSC), and the remaining nine steers served as noninfused controls. Nine in the second slaughter group of 18 were MPSC-infused, and nine were infused with the MPSC solution plus 500 ppm vitamin C (MPSC+C). The MPSC cattle had a 2.9% higher mean dressing percentage (P.05) on Warner-Bratzler shear force or USDA quality and yield grades. Results from a descriptive flavor profile sensory panel showed some significant differences in flavor profile characteristics, but these differences were small and inconsistent. Vascular infusion with MPSC or MPSC+C increased carcass weights, had few effects on USDA quality or yield grades or shear force, and had no consistent effects on flavor profile characteristics of cooked beef.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Vascular infusion; Flavor profile analysis